Association of tumor markers CA 15-3, CEA, and CA 125 with [18F]NaF PET findings in breast cancer patients - Naeimi, Arvin; Harsini, Sara; Derbekyan, Vilma; Abikhzer, Gad; Hickeson, Marc; Karls, Shawn; Abbaspour, Farzad (Frontiers in Oncology, 2025)
IntroductionBreast cancer often metastasizes to bone, and [18F]NaF PET is commonly used to detect skeletal involvement. This study examines the association of serum CA 15-3, CEA, and CA 125 with [18F]NaF PET findings in breast cancer to guide clinical decision-making.MethodsThis retrospective study included 360 breast cancer patients who underwent [18F]NaF PET. Associations between serum tumor markers (CA 15-3, CEA, CA 125) and [18F]NaF PET findings and lesion count were analyzed. Optimal cut-off values for predicting [18F]NaF PET positivity were determined using ROC analysis. Multivariable logistic regression identified independent predictors.ResultsAmong 360 patients (mean age 61.1 ± 13.9 years), median serum CA 15-3, CEA, and CA 125 levels were significantly elevated in patients with positive versus negative PET scans (all p<0.001). Marker levels revealed a dose–response relationship, rising with increasing numbers of skeletal lesions. In multivariable analysis, CA 15-3 (OR 1.053, p=0.002) and CEA (OR 1.264, p=0.001) independently predicted PET positivity, whereas CA 125 showed a marginal trend (p=0.081). ROC analysis identified optimal cut-offs of 19.25 U/mL for CA 15-3 (sensitivity 70.1%, specificity 90.4%, AUC 0.837) and 3.15 ng/mL for CEA (sensitivity 65.6%, specificity 85.2%, AUC 0.821). Combined model incorporating all three markers (probability cut-off 0.29) improved diagnostic performance (AUC 0.863; sensitivity 79.7%, specificity 92.3%). Invasive lobular histology and restaging indication were significant predictors of PET positivity.ConclusionElevated CA 15–3 and CEA independently predict [18F]NaF PET positivity in breast cancer. Optimal cut-offs were 19.25 U/mL for CA 15-3 (sensitivity 70.1%, specificity 90.4%, LR + 7.38, AUC 0.837) and 3.15 ng/mL for CEA (sensitivity 65.6%, specificity 85.2%, LR + 4.43, AUC 0.821). The clinical utility of CA 15–3 and CEA lies in rule-in and risk-stratification strategies. Patients above these thresholds, particularly those with invasive lobular carcinoma undergoing restaging, may benefit from prioritized [18F]NaF PET evaluation or improved interpretation of equivocal PET findings. CA 15–3 threshold, lower than routine laboratory reference, may guide aggressive screening and prioritized [18F]NaF PET in patients with high clinical suspicion. Multivariable model combining CA 15-3, CEA, and CA 125 (probability cut-off 0.29) improved diagnostic performance (sensitivity 79.7%, specificity 92.3%, AUC 0.863). Integrating CA 15–3 and CEA into clinical decision-making may enable a nuanced, risk-adapted approach, optimizing metastasis detection and resource allocation.